PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN (Students' Journal of Economic and Management, 2013)
Along with the progress of time lead to the development of technology. This phenomenon causes a company engaged in the field of photo printing services like Bahurekso Indah Foto Kaliwungu change the picture printing services from washing technique movies to digital techniques. This is done in order to enhance customer satisfaction while maintaining customer loyalty. This study discusses the effect of service quality on customer satisfaction and its impact on customer loyalty, as well as to test the mediation between service quality on customer loyalty with customer satisfaction as mediator variables were tested using path analysis (path analysis). Determination of the sample using purposive sampling method. Respondents in this study were 100 respondents with at least three visits to Bahurekso Indah Foto Kaliwungu. In this study, the data processing using the application SPSS (Statistical Package for Social Sciences). Analysis of the data includes quantitative and qualitative analysis. Quantitative analysis includes validity and reliability testing, the classic assumption test, multiple regression analysis, the test of Goodness of Fit through regression coefficient (R2), F test and t test. Qualitative analysis is the interpretation of the data obtained in the study by providing explanations on the data processing has been done. The results of this study indicate that the tested variables of service quality has a positive and significant impact on customer satisfaction and customer loyalty through the F test and t test. While the results of the test mediation path analysis (path analysis) there is indicate mediation effect.Key words : Service Quality, Customer Satisfaction, Customer Loyalty.